MEMBANGUN BUDAYA MUTU PADA LEMBAGA PENDIDIKAN ISLAM MENUJU MADRASAH UNGGUL - Amir, Amir (JURNAL AL-TANZIM, 2019)
This paper presents the efforts of madrasah in building a quality culture towards superior madrasah in Madrasah Aliyah Nurul Hikam, Kapongan, Situbondo. This is done in order to meet the complexity of the demands of society and respond to the changing times, especially in entering the era of the industrial revolution 4.0. The efforts made by Madrasah Aliyah Nurul Hikam in building a quality culture towards superior madrasah namely; 1) designing high performance-oriented attitudes and behavioral standards, both for the headmaster, administrative staff, teachers and students, 2) formulating the best service standards that must be obeyed by all madrasah residents to improve the quality of service to customers, especially students and parents, 3) integrating quality culture in all activities in madrasah, 4) giving awards to madrasah who have high achievements and providing guidance for those who have low performance, 5) providing motivation to madrasah to continue to improve their performance to suit the expectations of all parties, so that a superior madrasah quality can be created.